Binding of basal transcription factor TFIIH to the acidic activation domains of VP16 and p53. - Xiao, H (1994)
Acidic transcriptional activation domains function well in both yeast and mammalian cells, and some have been shown to bind the general transcription factors TFIID and TFIIB. We now show that two acidic transactivators, herpes simplex virus VP16 and human p53, directly interact with the multisubunit human general transcription factor TFIIH and its Saccharomyces cerevisiae counterpart, factor b. The VP16- and p53-binding domains in these factors lie in the p62 subunit of TFIIH and in the homologous subunit, TFB1, of factor b. Point mutations in VP16 that reduce its transactivation activity in both yeast and mammalian cells weaken its binding to both yeast and human TFIIH. This suggests that binding of activation domains to TFIIH is an important aspect of transcriptional activation.